Adsorber Particles with Magnetically-Supported Improved Electrochemical Conversion Behavior for Waste Water Treatment Processes - Schneider, Michael; Tschoepe, Andre; Hanselmann, Doris; Ballweg, Thomas; Cehermann, Carsten; Franzreb, Matthias; Mandel, Karl (Particle & Particle Systems Characterization, 2020)
Micron-sized supraparticles, consisting of a plurality of discrete nano- and microscale functional units, are assembled and fused by means of a droplet extrusion process. By combining nano magnetite, activated carbon, and conductive carbon with a polymeric binder matrix, particles are obtained which unite good magnetic properties, electrical conductivity, and adsorber activity through the high accessible surface area of the incorporated activated carbon of about 570 m2 g−1, thereby enabling a new approach toward sustainable water treatment processes. Due to the interplay of the components, it is possible to adsorb target substances, dissolved in the water which is demonstrated by the adsorption of the model dye methylene blue. A very fast adsorption kinetic and an adsorption capacity of about 400 mg g−1 is determined. By using the developed composite particles, it is also possible to electrochemically alter substances flowing through a magnetically-stabilized fluidized-bed reactor by electrochemically charging/discharging, significantly supported by the magnetic field enabling alternatingly optimum mobility/adsorption phases with contact/charging intervals. The electrochemical conversion can be increased up to 151% depending on the applied flow-rate and electrical voltage. By applying an external magnetic field, a further increase of electrochemical conversion of up to 70% can be observed.
CRIS-Team Scopus Importer:2020-04-02
Keywords: composite supraparticles; dye adsorption; electrochemical conversion; magnetic particles; water purification